Literature review: Peran bidan terhadap keberhasilan pemberian ASI Eksklusif - Maharani Maharani; Rizzatul Khumairoh (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: exclusive breastfeeding in Aceh in 2021 (66.66%) has increased compared to 2020 (65.43%), but there has not been a significant increase. Efforts are needed to increase exclusive breastfeeding. Exclusive breastfeeding is one way of good growth and development. In addition, midwives play an important role in the success of exclusive breastfeeding. Midwives are responsible for exclusive breastfeeding education and care for breastfeeding mothers during pregnancy, starting from the first breastfeeding to breastfeeding mothers. Midwife support can also give mothers the confidence to continue giving exclusive breastfeeding to their babies.Objectives: to review several journals about the role of midwives in the success of exclusive breastfeeding.Methods: this research is a descriptive analysis. This research in literature review held ini may-june 2021. The keywords used are the role of the midwife and exclusive breastfeeding. Literature sources were obtained from the Google Scholar, Science Direct, and Pubmed publication databases with the last five years limitation A total of 224 articles were obtained with these keywords, then were selected in stages according to predetermined criteria. Retrieved 10 articles published in 2015-2020. The articles obtained were compiled, analyzed, and concluded by looking for similarities, dissimilarities, giving views, comparing and summarizing.Results: literature studies show that there is a relationship between the role of the midwife and the success of exclusive breastfeeding. Providing education, information and assessment about exclusive breastfeeding is the responsibility of midwives to mothers starting from the period of pregnancy, the beginning of breastfeeding until the baby is 6 months old.Conclusion: the midwife has a role in the success of exclusive breastfeeding